Framing Analysis of Basuki Hadimuljono as Head of the Nusantara Capital Authority through Instagram in Supporting the Development of the Nusantara Capital City (IKN) in 2025 - Amansyah, Denny; Bizikrillah, Wahyu Arif; Alfayed, Zaki (Kemudi, 2026)
This study examines how Basuki Hadimuljono, as Head of the Nusantara Capital Authority, strategically employs Instagram to frame the development of Indonesia’s Nusantara Capital City (IKN) in 2025. Using a qualitative content analysis approach based on Entman’s four element framing model define problems, diagnose causes, make moral judgments, and treatment recommendations, the study analyzes selected Instagram posts featuring visual narratives, textual captions, and audience engagement. The results reveal that Basuki consistently frames IKN development by emphasizing sustainability, human resource development, cultural preservation, progress monitoring, and institutional legitimacy. Visuals and narratives highlight development achievements, ecological responsibility, moral ethical commitments, and concrete solutions, positioning IKN as a well managed, future oriented national project while reinforcing Basuki’s technocratic image. Public engagement, reflected in likes and comments, indicates that the framing successfully generates positive perceptions and trust toward IKN initiatives. The study contributes to digital political communication literature by demonstrating how visual based social media functions as a strategic tool for shaping public opinion, enhancing legitimacy, and mobilizing support for large-scale national projects